GEMCITABINE INDUCED DROP IN PLATELET COUNTS: A CASE REPORT - O, Balaji; D, Amita; RT, Sereen; P, Navin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Chemotherapy with anticancer drugs is known to be beneficial, but like a double-edged sword it as its own demerits in form of adverse effects. Cancer chemotherapy induced thrombocytopenia is troublesome and platin based regimens namely Carboplatin and Cisplatin is known to cause it very commonly. Gemcitabine, in combination with platinum compounds is known to cause severe thrombocytopenia. Hence, we report a case of thrombocytopenia induced by Gemcitabine when used as single agent in treatment of ovarian cancer. Â 